Diagnóstico de la educación técnica en Perú: alcances para el desarrollo de programas en gestión - Regalado-Pezúa, Otto (2019)
The main objective of this article is to know the current situation of technical higher education in Peru, in particular in management programs. To do this, using secondary sources and in-depth interviews with experts, an exploratory work was carried out that consisted of analyzing from the point of view of demand, where the technical training needs that the market requires were observed; as well as, an analysis from the point of view of the offer, where the development and investment opportunities were observed, in particular of the private offer, to cover the gap of unsatisfied needs of the employers.